Social Bonding, Early School Leaving, and Delinquency - Marie Olivier
In this paper we investigate how successful social bonding theory is at predicting juvenile delinquency and school dropout behaviour. We adopt a simple dynamic approach which assumes that past involvement in risky behaviour reduces individual restraints for future participation in risky behaviour. We use a ten years education panel following Dutch adolescents who participated in a survey in their first year of high school in 1999. This information was matched to annual information on police arrests based on registry data. Our results show that school performance (as measured by test scores) is the key social bond element preventing young people from engaging in risk behaviour. We also find that involvement in past risky behaviour increases the likelihood of future missteps and that the protective influence of school performance is mitigated.labour economics ;